Analisis Risiko Rantai Pasok Susu pada CV Nature Safe Jaya Kabupaten Banyuwangi Provinsi Jawa Timur - PAKSONO, ROZAAN; AMBARAWATI, I G.A.A.; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
Diary Supply Chain Risk Analysis at CV Nature Safe Jaya Banyuwangi Regency East Java Province.  Livestock is an agricultural sub-sectors that produces milk to fulfill needs of animal protein for the community. CV Nature Safe Jaya is a milk producing company located in Songgon District, Banyuwangi Regency, East Java Province. It’s milk production activities involve the supply chain. This research aims to identify risks that may arise and formulate mitigation as an effort to reduce the company’s supply chain risks. Data and information were obtained from key informants and all company employees as respondents. This research uses the Supply Chain Operation Reference (SCOR) method to analyze risk in the company's supply chain with a plan, source, make, deliver, and return framework. The identified risks were further analyzed using the Failure Mode Effect Analysis (FMEA) method to determine risk management priorities with a Risk Priority Number (RPN). The results showed that 13 risk events and 36 risk agensts were identified in the SCOR framework. There are five mitigation plans that can be formulated, namely (1) how to make improvements in the recording of the calculation of the amount of feed needed, (2) conduct periodic forage price surveys, (3) search for reserves/alternatives for other concentrate feed suppliers, (4) consider adding assets for the company, (5) tightening of checks before shipping.